PEMAKAIAN KONTRASEPSI PIL DAN SUNTIK MENAIKKAN pH DAN VOLUME SALIVA: CONTRACEPTIVE PILL AND INJECTION INCREASE pH AND VOLUME OF SALIVA - Juni Handajani; Rini Maya Puspita; Rizki Amelia (Dentika: Dental Journal, 2010)
Saliva is the mixture of oral fluid, that has function to protect the oral cavity. Hormonal contraception is very popular in Indonesia to avoid pregnancy. This study aimed to evaluate salivary volume and pH of woman who taking contraceptive pill and by injection. The design of study was a cross sectional . The subjects were 30 women, 20-35 years old, with the approval of ethical clearance from Ethic Comittee Medical Faculty of Gadjah Mada University. The subjects were divided into 3 groups (taking contraceptive pill, by contraceptive injection and control) that each group consisted of 10 women. The criteria of subjects were healthy, no orthodontic treatment, no prothesa or crown, and taking hormonal contraception more than 3 months. Saliva samples were collected in the afternoon (16.00-18.00 pm) for 1 minute using unstimulating method. Data analysis using ANOVA test (p<0,05). The results showed that there were significant differences in salivary pH and volume. As conclusion, hormonal contraceptive can increase salivary pH and volume.